Analisis Perbandingan Asam Lemak VCO dengan Metode Fermentasi dari Berbagai Varietas Kelapa - Ardianto, Ardianto; Mutiah, Haerul (BIOEDUSCIENCE, 2018)
Virgin Coconut Oil (VCO) is one of coconut processed products which contains various health benefits; but no any diversification of coconut processed product in regency of Bulukumba. The aim of this research is to investigate the comparison of VCO fatty acid composition through fermentation method from coconut varieties in district of Kajang, regency of Bulukumba. The sample of the research was the VCO varieties taken from various coconuts, there were 9 samples which represent the each variety of green coconut, red coconut and hybrid coconut. The sampling used proportional random sampling technique. Technique of collecting data, the data was collected by the analyst in LPPT of UGM by using gas chromatography method in an experiment. The collected data was analyzed descriptively by comparing the SNI 7381-2008. The result indicated that the highest mean percentages in green coconut werelauric and caproat acid, while the highest percentages in hybrid coconut werepalmitic acid, stearic acid, oleic acid and myristic acid, and the highest percentage in red coconut was capra acid. The composition of fatty acid from the three coconut varieties showed no significant difference; where lauric acid was 0.58%-2.75%, caproat acid was 0.01% - 0.04%, palmitic acid was 1.07% - 1.5%, stearic acid was 0.66% - 0.09%, oleic acid was 0.58% - 1.3%, myristic acid was 2.92% - 3.48% and copra acid was 0.1% - 1.9%. While the linoleic and linolenic acid had the same percentage. The difference of the fatty acid composition showed that, in generally, the composition of each coconut varieties fulfilled the SNI 7381-2008.